Patient-prosthesis mismatch in the context of surgical aortic valve replacement with the Trifecta bioprosthesis - Alvajärvi, Arvi (My University, 2020)
Surgical aortic valve replacement (SAVR) is widely used for the treatment of aortic valve diseases. Each valve prosthesis has individual hemodynamic characteristics, which may have implications in the clinical outcome of patients. This review considers the hemodynamic performance of the St. Jude Medical Trifecta biological aortic valve prosthesis early after surgery. An essential method to determine hemodynamic parameters after SAVR is transthoracic echocardiography (TTE) that can be used to measure transvalvular flow velocities and pressure gradients. Patient-prosthesis mismatch (PPM) occurs when the orifice of the implanted prosthesis is too narrow relative to the patient’s body surface area. Postoperative PPM is thought to have a negative effect on the outcome after SAVR. The aim of this review is to summarise the current hemodynamic data of the Trifecta biological prosthesis in the aortic position. A systematic review of the literature was conducted through Pubmed, Scopus, Science Direct and Google Scholar with terms ‘‘effective orifice area”, “hemodynamic”, “gradient” combined with “Trifecta” or “Perimount”. This yielded 276 articles, 18 of which were included into a recently conducted meta-analysis. Out of those studies, ten evaluated the hemodynamics and outcome of more than 100 patients with the Trifecta prosthesis. Each of the studies showed excellent early hemodynamic results with relatively small incidence of PPM for the aortic bioprosthesis Trifecta. Moreover, the hemodynamic parameters of the Trifecta bioprosthesis seemed favourable when compared to other widely used biological valves.
Keywords: Aortic valve, Patient-prosthesis mismatch, PPM, Trifecta, Effective orifice area